If the sum of three times a number and -5 is multiplied by 6, the answer is 42. Find the number.

x = the number

6[3x + (-5)] = 42 {sum of three times a number and -5 is multiplied by 6, answer is 42}

6(3x - 5) = 42 {simplified signs in brackets}

3x - 5 = 7 {divided each side by 6}

3x = 12 {added 5 to each side}

x = 4 {divided each side by 3}

6[3x + (-5)] = 42 {sum of three times a number and -5 is multiplied by 6, answer is 42}

6(3x - 5) = 42 {simplified signs in brackets}

3x - 5 = 7 {divided each side by 6}

3x = 12 {added 5 to each side}

x = 4 {divided each side by 3}

**the number is 4***Ask Algebra House*